Business Model Canvas and Strategic Model Canvas: contributions to refresh the way managers strategize - Mancini de Azevedo, Pedro Henrique; Vasconcelos Silva, Simone (Revista Gestão da Produção Operações e Sistemas, 2022)
Objective: The purpose of this paper is examining the application experiences on the use of the Business Model Canvas and the Strategic Model Canvas, in order to know whether both tools can renew the managers’ ways of strategizing. Originality/value: Our paper brings contributions to the strategy-as-practice paradigm by suggesting new practices and combinations between strategy ‘soft’ tools and analytical tools. Design/methodology/approach: Using an action research method, we have followed the strategy process of four Brazilian companies. Results: We have shown empirical evidences that the combined use of the Business Model Canvas and the Strategic Model Canvas has helped managers to understand and solve strategic problems in a way that other traditional strategy tools haven’t. Keywords – Business Model Canvas; Strategic Model Canvas; Strategy-as-practice.